2020
DOI: 10.1016/s0140-6736(20)30553-5
|View full text |Cite
|
Sign up to set email alerts
|

Health security capacities in the context of COVID-19 outbreak: an analysis of International Health Regulations annual report data from 182 countries

Abstract: Background Public health measures to prevent, detect, and respond to events are essential to control public health risks, including infectious disease outbreaks, as highlighted in the International Health Regulations (IHR). In light of the outbreak of 2019 novel coronavirus disease (COVID-19), we aimed to review existing health security capacities against public health risks and events. MethodsWe used 18 indicators from the IHR State Party Annual Reporting (SPAR) tool and associated data from national SPAR rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
503
1
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(550 citation statements)
references
References 14 publications
11
503
1
17
Order By: Relevance
“…A study with 182 countries found that 33% had low capacity to respond to a public health event, and 24% had little available functional capacity, even with the support of funds coming from elsewhere. These events include infectious diseases 30 . In this study, females believed to have a high risk of infection by coronavirus (Table 1), which is explained due to the greater sense of self-care among women 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A study with 182 countries found that 33% had low capacity to respond to a public health event, and 24% had little available functional capacity, even with the support of funds coming from elsewhere. These events include infectious diseases 30 . In this study, females believed to have a high risk of infection by coronavirus (Table 1), which is explained due to the greater sense of self-care among women 31 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Compared with developed areas, countries or territories in the Western Pacific Region have insufficient health-care resources, and relatively low detection and prevention capacity. 4 Although these countries or territories have just a few confirmed infected people, without adequate control and preparedness, large-scale community transmission of COVID-19 is likely to occur. Fortunately, countries such as Fiji have already started to monitor high-risk persons and strengthen the management of international borders.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the number of exposure events at the on 28 th April was considered to be 2.5 considering the prolonged duration of awareness and practice on Social distancing. 4. The fourth intervention was to release lock-down for 1 week after 14 th April for 7 days and then again continue it for another 21 days till 12 th May, 2020 with a similar increase in bed capacity as mentioned earlier.…”
Section: Adding Interventions To the Modelmentioning
confidence: 96%
“…13.8% progress to severe disease and 6.1% become critically ill with respiratory failure, septic shock or multi-organ failure [1]. However, detection and response capacity of COVID-19 cases globally vary across all countries [4]. In a country like India with a varied administrative set-up and state policies, healthcare amenities vary even further [5].…”
Section: Introductionmentioning
confidence: 99%